Clinicoetiological profile of urinary tract infection in pediatric population in a teaching hospital in south India - Venugopal, Poornima; Cherian, Carol Sara; Raghunath, Pooja (International Journal of Contemporary Pediatrics, 2021)
Background: Urinary tract infection (UTI) is one of the most common bacterial infections seen in children. A wide range of organisms with varying antibiotic sensitivity patterns have been known to cause UTI. The objective of the study was to analyse the clinical presentation of UTI in children between 1-month to15 years of age and to analyse the causative microorganism and their drug susceptibility in UTI in children between 1 month to 15 years of age. Methods: A retrospective study was conducted in a teaching hospital in Kerala, between July 2018 and June 2020 among children 1 month to 15 years of age who presented with symptoms of UTI. Patients who had culture positive UTI were included in the study. Clinical data was obtained from inpatient and outpatient records. Antimicrobial susceptibility was done for positive urine culture by Kirby-Bauer disk diffusion method. Statistical analysis was done using Statistical package for social sciences (SPSS) software version 16. Results: Of the 1057 urine samples analysed, 18.44% had significant bacteuria. 43.07% were children less than one year of age with male predominance. Fever and dysuria were the most common clinical presentation. E. coli was the most prevalent pathogen isolated followed by Klebsiella pneumoniae. Enterococcus faecalis was the only gram-positive bacilli isolated. Highest resistance was shown to ampicillin, third generation cephalosporins and co-trimoxazole. Least resistance was shown to nitrofurantoin, fluoroquinolones, aminoglycosides, piperacillin- tazobactam and carbapenems. Conclusions: Regular surveillance programme is necessary for implementation of guidelines for empiric treatment of UTI.